Pendidikan Karakter Peduli Lingkungan dan Menjaga Kebersihan di UPT SDN 066048 Medan - Annisa Amanda Putri; Husni Thamrin (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Character is something that exists in every individual who is formed in the family environment since childhood. Good character can be formed through education, one of which is through character education in schools. One of the characters that must be formed from an early age is the character of caring for the environment. The practitioner is interested in doing the second Field Work Practice in class IV at UPT SDN 066048, based on observations made by the practitioner in class IV, they are less sensitive to the surrounding environmental conditions. They still often throw garbage carelessly, don't wash their hands after handling dirty objects and are not disciplined about self-grooming such as worn and dirty uniforms, unclean fingernails, and so on. The practice in this study used the groupwork method and used a descriptive qualitative approach with a case study approach. The implementation of the Field Work Practice activities was carried out for approximately four months to see whether the objectives of the program were achieved. It is expected that class IV students at UPT SDN 066048 can have the character of caring for the environment, and know how to protect and love the environment.